ANALISIS KEPUASAN SISWA SMK NEGERI 1 GUNUNG SINDUR PADA PELAJARAN MATEMATIKA DENGAN MENGGUNAKAN METODE SERVQUAL - Febiyansyah, Febiyansyah; Arofah, Irvana (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to analyze the satisfaction level of 10th and 12th-grade students at SMK Negeri 1 Gunung Sindur regarding Mathematics lessons using the SERVQUAL (Service Quality) method. The background of this research lies in the importance of understanding students’ perceptions of the quality of Mathematics instruction to enhance learning effectiveness. The SERVQUAL method was chosen for its capability to measure the gap between students’ expectations and perceptions of the services provided. Research data were collected from 10th and 12th-grade students at SMK Negeri 1 Gunung Sindur. Data analysis was conducted using the SERVQUAL method with the aid of SPSS Version 16 statistical software and Microsoft Excel. The findings of this study are expected to identify the dimensions of service quality in Mathematics learning that exhibit the largest gaps between student expectations and perceptions, as well as the dominant factors influencing student satisfaction. The implications of this research are to provide valuable input for the school, particularly for Mathematics teachers, to formulate strategies for improving teaching quality that are more focused on aspects most in need of improvement, ultimately leading to optimal student learning satisfaction.